Особливості морфоструктури пагонової системи Phaedranassa cinerea Ravenna (Amaryllidaceae) - Zhila, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The connection between the structure of a bulb of Phaedranassa cinerea Ravenna and ecological and geographical conditions of growth is established.